Strategic management and job satisfaction in the initial educational institution Nº141 "Heroes de Jactay", Moras-2019 - Urdanivia-Ramírez, María del Pilar (2023)
The general objective of this research was to determine the relationship between the strategic institutional management and job satisfaction of teachers of the Initial Educational Institution Nº141 "Héroes of Jactay", Moras-2019. The present investigation used the type and level of basic and descriptive correlational research. The research design was non-experimental and transversal. The study population consisted of 15 teachers; Likewise, the sample was population-based because 100% of the members were taken because they were very small. The survey technique was used, whose instruments were the "Institutional Strategic Management Questionnaire" and the "Job Satisfaction Questionnaire", which were validated through expert judgment. On the other hand, the data processing was carried out with the help of the statistical program SPSS version 22 and the Excel 2013 program, which were presented in tables and graphs with their respective interpretations. According to the statistical results, the Correlation Coefficient was 0.878, being a high and positive correlation between the two variables. Also, in our hypothesis test, the statistical value t = 6,630, in the graph it is located to the right of tc = 2,131 which is the rejection zone, then we discard the null hypothesis and accept the alternate hypothesis.